Efficiency of Increasing Working Capital for MSMEs in Tanjung Jabung Timur - sarmiati sarmiati; M Nazori Madjid; Sayyid syekh (STIE Syari'ah Al-Mujaddid Tanjung Jabung Timur, 2022)
Working Capital Efficiency is the accuracy of the way (effort and work) in carrying out something that does not waste time, energy, cost and usefulness related to the use of working capital, namely trying to ensure that the available working capital is neither excess nor deficiency. The importance of this working capital efficiency analysis for the growth of superior SMEs in East Tanjung Jabung, the researchers conceptualized research on working capital efficiency in East Tanjung Jabung. This study uses a qualitative approach with a descriptive model. The informants used in this study consisted of 12 business actors in the MSME sector. The analysis used in this research is data reduction, data presentation, and conclusion drawing. The data findings show the harmony between the supporting theory and the reality in the field that efficient working capital will determine profits. This finding encourages MSME actors and the government to always pay attention to their working capital and financial management. Furthermore, to improve the MSME sector, of course, the entrepreneurial spirit of the community is also needed so that new entrepreneurs can emerge who can create business activities and create jobs.